The Characteristics of the South Yellow Sea Foreland Basin and Its Tectonic Evolution - Hong Xu; Yazeng Ma; Guangyou Zhu; Dapeng Su; Baohua Lei; Guoqing Zhang; Bolin Zhang; Weiwei Zhang; Wei Yan (Journal of Marine Science and Engineering, 2025)
The first oil and gas well in the South Yellow Sea Basin was completed in 1961. In 1984, 2.45 tons of light oil were obtained from the Cenozoic strata. However, it remains the only large oil and gas basin in China’s offshore area without industrial oil and gas discoveries. Although the consensus is that the South Yellow Sea Basin is a foreland basin, and the oil and gas exploration prospects are promising, the research on the regional structure and the tectonic evolution of the foreland basin system is weak, which seriously hinders the process of industrial oil and gas discoveries. This paper reports the results of over 30 years of onshore and offshore investigations and well-seismic joint interpretation in the study area: for the first time, the mountains and basins formed by the collision of the North China and Yangtze plates were discovered in the geological survey of the northern islands of the South Yellow Sea Basin; the C-type eclogite chronology of Qianliyan Island, the characteristics of the foreland basins and intracontinental foreland basins around the South Yellow Sea, and the tectonic evolution characteristics and models of the basins were clarified. Through the zircon/phosphate fission track analysis of the deep black Jurassic strata in the Qianyuan S-2 well, it was revealed that the collision and subduction of the Pacific Plate against the Eurasian Plate since the Late Cretaceous–Paleogene led to large-scale uplift movements, and more than 3000 m of strata were eroded in the basin area. This is consistent with the multiple unconformities of E/N, K/N, and T2/N identified by well-seismic joint interpretation, and is also the main reason why oil and gas have been difficult to preserve in the South Yellow Sea Basin since the Middle Triassic–Jurassic. Deep prototype oil and gas exploration in the basin may be the preferred option for current oil and gas exploration deployment, which is conducive to achieving industrial oil and gas discoveries.